STRATEGI PENDIDIKAN DIGITAL UNTUK PENGUATAN UMKM MENUJU PASAR GLOBAL - Raynaldi Wisnu Wibowo; Moh Anas Al Hibrizi; M. Asif Nur Fauzi (Educatus, 2024)
The development of the digital economy has created both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) to compete on a global scale. Amid this transformation, digital education plays a crucial role in equipping MSME actors with the knowledge and skills needed to optimally utilize technology. This study aims to analyze various digital education strategies that can be applied to enhance the capacity of MSMEs in facing the era of digitalization. The research method used is a literature review and descriptive analysis of various digital training programs implemented in different regions. The results show that the integration of digital literacy, e-commerce training, and the use of data analytics are key strategies in developing resilient and competitive MSMEs in the global market. In addition, support from educational institutions, the government, and the private sector is essential in building an inclusive and sustainable digital education ecosystem. With the right strategy, digital education has the potential to become a driving force in empowering MSMEs towards sustainable global transformation.